ECONOMIC EFFECTS REAL ESTATE TAX - Tadić, Milan (ECONOMICS - INNOVATIVE AND ECONOMICS RESEARCH JOURNAL, 2016)
The real estate tax is usually a fiscal instrument which performs the property tax. When it comes to real property or immovable this term include: apartments, houses, land, cottages, excess housing landscape and more. The real estate tax as a form of the fiscal charges ownership or use of certain forms of real estate, and the revenue from this tax is levied on the area where the property is located regardless of the place of residence of its owner. The tax base for the calculation of this tax usually consists of the market, estimated or annuity value of certain real estate. This form of taxation in the Republic of Serbian applies from 1.1.2012. , and its introduction has been replaced by former property taxes. The diﬀerences between the two concepts mentioned taxes are numerous and significant. Among the more important are: subject to taxation under the new concept of the real estate rather than law, a taxpayer is any property owner rather than the holder of rights to immovable property tax base is the market value of real estate which is replaced by the payment of taxes per square meter of usable area, the rate of property tax is determined local government, which can not be lower than 0.05% of the estimated value of the real estate nor higher than 0.5% of the appraised value of real estate. The last change, ie. The new law on Property Tax from 5.11.2015. was determined by the tax rate to 20%. The fact that local governments each of them determines the tax rate on real estate which range from high to low rates of multiple, makes this tax is progressive. Progression is particularly expressed in the distinction applied tax rates of developed and undeveloped municipalities, where we have a case that less developed tolerate a higher tax burden, which leads to negative economic eﬀects. However, real estate tax has its own economic and social characteristics which must be aligned with the objectives of tax policy. This means that the real estate tax should be considered from the standpoint of the entire tax system and not from the standpoint of individual income tax forms.